Maritime English Language Restrictedness - Kovacevic, Sanela (European Journal of Social Science Education and Research, 2022)
Maritime English is a specific register. Therefore, it requires a specific treatment. This paper implies the restricted aspect of a complex system such as English for specific purpose in the nautical education and profession. The sophisticated system of the maritime English makes it a plain instrument of communication. The opposite "tides" govern the system: creative and economical tendency. The creative side of the maritime language is evident in the forming of new words and meanings, combining of existing units, various metaphors, etc. We have tried to look into certain subregisters within Standard Marine Communication Phrases (SMCP) by pointing to the main characteristics. Seaspeak is a vital instrument of communication on board a ship. The importance of English language has always been emphasized, especially the importance of the standardized maritime phrases used in vessel-to-vessel vessel-to-port communication. By trying to encode the Maritime English world, we will look into the structure of Maritime English communication terms and phrases. However, we cannot make artificial borders between Maritime and General English. These two registers intertwine and it is impossible to eliminate Maritime English from General English and vice versa. As far as restricted aspect of Maritime English is concerned, Standard Marine Communication Phrases are used in both ship-to-ship and ship-to-shore communication.